2017
DOI: 10.1038/s41598-017-15992-4
|View full text |Cite
|
Sign up to set email alerts
|

Maraba virus-vectored cancer vaccines represent a safe and novel therapeutic option for cats

Abstract: Direct killing of malignant cells combined with induction of tumour-specific immune responses makes oncolytic vaccines attractive for cancer therapy. We previously developed a heterologous cancer immunization strategy that utilized a replication-defective adenovirus-vectored primary vaccine encoding a tumour antigen followed by boosting with a replication-competent Maraba virus expressing the same antigen. To assess the safety of oncolytic Maraba virus-based booster vaccines and inform the design of clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…We also found that the OVs were mostly found in tumor tissues or the peri-tumoral region in the lung slices ( Figures 5 C and 6 C), as has also been well established in the literature. 53 , 54 , 55 , 56 , 57 , 58 Moreover, we observed a decrease in tumor tissue metabolic activity when in the presence of oncolytic vector MG1-eGFP, using the resazurin assay, a surrogate tool for viability ( Figure S3 ). Therefore, this protocol is a convenient tool to assess the activity of other gene and OV vectors prior to and to complement in vivo work.…”
Section: Methodsmentioning
confidence: 84%
“…We also found that the OVs were mostly found in tumor tissues or the peri-tumoral region in the lung slices ( Figures 5 C and 6 C), as has also been well established in the literature. 53 , 54 , 55 , 56 , 57 , 58 Moreover, we observed a decrease in tumor tissue metabolic activity when in the presence of oncolytic vector MG1-eGFP, using the resazurin assay, a surrogate tool for viability ( Figure S3 ). Therefore, this protocol is a convenient tool to assess the activity of other gene and OV vectors prior to and to complement in vivo work.…”
Section: Methodsmentioning
confidence: 84%
“…To further consolidate the immunotherapeutic activity of oncolytic vesiculoviruses, we and others have equipped their genome with transgenes overexpressing tumor antigens. 18 , 20 , 25 , 26 , 33 42 The resulting so-called “oncolytic vaccine” aims at potentiating the adaptive arm of antitumor immunity.…”
Section: Introductionmentioning
confidence: 99%
“… 45 Additionally, with the aim of extending the Ad:MG1 vaccination to the treatment of veterinary cancer patients, we characterized its safety and tolerability profiles in healthy tumor-free outbred cats. 33 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations